PROSEDUR PENGIRIMAN BARANG PADA PT POS INDONESIA (PERSERO) KANTOR POS JAKARTA SELATAN - Wibowo, Hadi; Handayani, Eka Putri; Wijaya, Darma; Octaviani, Tania (Yayasan Akrab Pekanbaru, 2019)
Delivery service is one of service media that helps to facilitate customer in delivery such as delivery of goods and important documents at an affordable cost and time predetermined. PT Pos Indonesia (Persero) One of the company owned by state owned enterprises (BUMN) engaged in the delivery service of national and international post. The subject matter in this study is to discuss the procedure of delivery of goods. In conducting this research using qualitative data types with descriptive analytical techniques, the type of delivery service is the Post Express service package, Special Flash post package, regular postal package and express mail Service (EMS). Transportation mode Used by land, sea and air. As for the related parts in the delivery procedure is the sorting section, the Puri submit section, the castle part of the receive and the parcel. Documents used in the delivery procedure are the Register sheet, CN-23, R-7, postal cover, manifest handover, manifest accept and proof of delivery. The procedure of delivery of goods at PT Pos Indonesia (Persero) has a flowchart that goes well and PT Pos Indonesia (Persero) has a procedure that has been arranged systematically.